2019
DOI: 10.1002/aenm.201900429
|View full text |Cite
|
Sign up to set email alerts
|

Realizing Ultrafast Oxygen Evolution by Introducing Proton Acceptor into Perovskites

Abstract: The oxygen evolution reaction (OER) is of prime importance in multiple energy storage devices. Perovskite oxides involving lattice‐oxygen oxidation are generally regarded as highly active OER catalysts, but the deprotonation of surface‐bound intermediates limit the further activity improvement. Here, it is shown that this kinetic limitation can be removed by introducing Sr3B2O6 (SB) which activates a proton‐acceptor functionality to boost OER activity. As a proof‐of‐concept example, an experimental validation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
87
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 42 publications
1
87
0
Order By: Relevance
“…Meanwhile, the ECSAs were significantly increased in both the Ni‐exsolved CaTiO 3 prepared by solid‐state reactions and solvothermal synthesis, but the latter (16.82 cm 2 ) was higher than the former (14.87 cm 2 ) (Figure a) (previous metal: >30 cm 2 , transition metal oxides: ≥1 cm 2 , and perovskites: ≈3 cm 2 depending on synthesis methods) . The geometric OER activities were 3.28 mA cm −2 geo , 4.80 mA cm −2 geo , and 10.88 mA cm −2 geo at 1.7 V in the mixture, solid state prepared micrometer scale Ni‐exsolved, and Ni‐exsolved CaTiO 3 sub‐micrometer spheres by solvothermal synthesis, respectively (Figure b), which is comparable to state of the art results of both base metals and perovskites (Table S3, Supporting Information) . The results clearly show that the increase in Ni utilization from the porous sub‐micrometer spheres can enhance the electrochemical activities.…”
Section: Resultsmentioning
confidence: 97%
“…Meanwhile, the ECSAs were significantly increased in both the Ni‐exsolved CaTiO 3 prepared by solid‐state reactions and solvothermal synthesis, but the latter (16.82 cm 2 ) was higher than the former (14.87 cm 2 ) (Figure a) (previous metal: >30 cm 2 , transition metal oxides: ≥1 cm 2 , and perovskites: ≈3 cm 2 depending on synthesis methods) . The geometric OER activities were 3.28 mA cm −2 geo , 4.80 mA cm −2 geo , and 10.88 mA cm −2 geo at 1.7 V in the mixture, solid state prepared micrometer scale Ni‐exsolved, and Ni‐exsolved CaTiO 3 sub‐micrometer spheres by solvothermal synthesis, respectively (Figure b), which is comparable to state of the art results of both base metals and perovskites (Table S3, Supporting Information) . The results clearly show that the increase in Ni utilization from the porous sub‐micrometer spheres can enhance the electrochemical activities.…”
Section: Resultsmentioning
confidence: 97%
“…where ρ RHE is the proton reaction order 11,14,17 . When the deprotonation processes are strongly coupled with an electron transfer, its OER kinetics shows little dependence on the pH value of a solution (vs. RHE), leading to a low ρ RHE value.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, if the deprotonation process is involved in the PDS along with decoupling of the electron transfer process, the OER kinetics depends strongly on pH with a larger ρ RHE value. For instance, it was observed that various mixed ionic-electronic conductors (MIECs) (i.e., =La 0.5 Sr 0.5 CoO 3 and Pr 0.5 Ba 0.5 CoO 3 ) have lattice oxygen participation in the OER, leading to a decoupled proton-electron transfer process in OER and a strong pH dependence 15,17,38,39 .…”
Section: Resultsmentioning
confidence: 99%
“…[ 30–33 ] On the other hand, the hybrid systems can induce some synergetic effects enabling to stabilize catalytic sites, and achieve a desirable electrocatalytic stability. [ 34,35 ] Therefore, we believe that the formation of RP/perovskite hybrid may be a viable way to regulate the electronic structure and accordingly boost the electrocatalytic performance. However, such hybrid system for OER has never been explored, and a simple synthetic process for RP/perovskite hybrid is also highly needed.…”
Section: Figurementioning
confidence: 99%